Pelatihan Usaha Ekonomi Produktif Anggota PKK Desa Rejoslamet, Kec. Mojoagung, Kab. Jombang - hartono, hartono; rahayu, Rahayu; Rudianto, Adik; nersiwad, Nersiwad (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
ABSTRACT The purpose of conducting productive economic business training for PKK members, women home workers carried out by the Jombang Regency Women's Empowerment and Child Protection Service is to help improve the economy and family welfare. The training on productive economic business in the form of training on making wallets and bags from leather was attended by 25 participants consisting of: 1) PKK members, 2) Female cadres of Rejoslamat village, Mojowarno District, Jombang Regency. The training method is carried out by direct practice method by bringing in experts in making bags and wallets, and questions and answers. The results of the training on productive economic efforts for PKK members and female cadres, the training participants were very enthusiastic to participate and actively dialogued about how to implement the right marketing strategies for the results of their activities.